Hybrid Membranes of the Ureasil-Polyether Containing Glucose for Future Application in Bone Regeneration - da Silva, Camila Garcia [UNESP]; Monteiro, João Rodrigues [UNESP]; Oshiro-Júnior, João Augusto; Chiavacci, Leila Aparecida [UNESP] (MDPI, 2023)
The application of mesenchymal stem cells (MSC) in bone tissue regeneration can have unpredictable results due to the low survival of cells in the process since the lack of oxygen and nutrients promotes metabolic stress. Therefore, in this work, polymeric membranes formed by organic–inorganic hybrid materials called ureasil-polyether for modified glucose release were developed in order to overcome the problems posed by a of lack of this nutrient. Thus, membranes formed by polymeric blend of polypropylene oxide (PPO4000) and polyethylene oxide (PEO500) with 6% glucose incorporation were developed. Physical–chemical characterization techniques were performed, as well as tests that evaluated thermal properties, bioactivity, swelling, and release in SBF solution. The results of the swelling test showed an increase in membrane mass correlated with an increase in the concentration of ureasil-PEO500 in the polymeric blends. The membranes showed adequate resistance when subjected to the application of a high compression force (15 N). X-ray diffraction (XRD) evidenced peaks corresponding to orthorhombic crystalline organization, but the absence of glucose-related peaks showed characteristics of the amorphous regions of hybrid materials, likely due to solubilization. Thermogravimetry (TG) and differential scanning calorimetry (DSC) analyses showed that the thermal events attributed to glucose and hybrid materials were similar to that seen in the literature, however when glucose was incorporated into the PEO500, an increase in rigidity occurs. In PPO400, and in the blends of both materials, there was a slight decrease in Tg values. The smaller contact angle for the ureasil-PEO500 membrane revealed the more hydrophilic character of the material compared to other membranes. The membranes showed bioactivity and hemocompatibility in vitro. The in vitro release test revealed that it is possible to control the release rate of glucose and the kinetic analysis revealed a release mechanism characteristic of anomalous transport kinetics. Thus, we can conclude that ureasil-polyether membranes have great potential to be used as a glucose release system, and their future application has the potential to optimize the bone regeneration process.
Keywords: bone regeneration; glucose release; organic–inorganic hybrids; polyethylene oxide; polypropylene oxide; sol–gel process